Optimization and modelling using the response surface methodology (RSM) for ciprofloxacin removal by electrocoagulation - Barisci, Sibel; Turkay, Ozge (Iwa Publishing, 2016)
In this study, response surface methodology (RSM) was used to investigate the effects of different operating conditions on the removal of ciprofloxacin (CIP) by the electrocoagulation (EC) with pure iron electrodes. Box-Behnken design was used for the optimization of the EC process and to evaluate the effects and interactions of process variables such as applied current density, process time, initial CIP concentration and pH on the removal of CIP by the EC process. The optimum conditions for maximum CIP removal (86.6%) were found as pH = 4; C-o = 5 mg.L1-; I-d = 4.325 mA.cm(2-); t(process) = 10 min. The model adequacy and the validity of the optimization step were confirmed with additional experiments which were performed under the proposed optimum conditions. The predicted CIP removal as 86.6% was achieved at each experiment by using the optimum conditions. These results specify that the RSM is a useful tool for optimizing the operational conditions for CIP removal by the EC process.
Keywords: ciprofloxacin; electrocoagulation; process optimization; RSM